Formation of base populations of meat-type chickens. IV. Evaluation of female line from productive and reproductive traits - Schmidt, Gilberto Silber; Packer, Irineu Umberto; Duarte, Francisco Alberto de Moura; Costa, Cláudio Nápolis; Ávila, Valdir S. de (Pesquisa Agropecuaria Brasileira, 1991)
This study was carried out at Centro Nacional de Pesquisa de Suínos e Aves (National Swine and Poultry Research Center) of EMBRAPA with the objective of testing four commercial lines of meat-type chickens using diallel crosses. There were four female lines identified by P1, P2, P3 and P4. The characteristics fertility, hatchability, birth rate and egg production were evaluated. There were significant differences among crosses for egg production, hatchability and birth rate. The reciprocal effects were significant for all traits except hatchability. General combining ability was significant for all characteristics evaluated. Specific combining ability and reciprocal effects were insignificant for both fertility and hatchability. Heterosis effect was significant for productive characteristics, varying between 1.88% and 11.63% and from 1.02% to 12.02%, respectively for egg production/hen/day and egg production/caged hen. Commercial P1, P2 and P3 appear to be those most appropriate for the formation of the base population of the female line.